Necessidades de informação dos usuários do site Lupus Online: um estudo dos pacientes - Ana Cristina Morado Nascimento Frade (2004)
The object of study of this work is the informational behavior of users of health websites focusing the research in the Lupus OnLine case. Refers to the identification of the most important features founded in the messages forum and the informational needs of users of this website, considering that all of them derive from specific questions and personal desire of each user in sharing his individual context. The content analysis method allowed the identification of categories and subcategories that characterize in a systematic way the informational flow presents in this communicational channel. Information seeking and use in the everyday-life, the social context and Brazilian reality that health and their agents are part of it, the understanding of new informational environment created by Internet and his users orient the development of this work.